Unravelling the distinct surface interactions of modified graphene nanostructures with methylene blue dye through experimental and computational approaches - Manappadan, Zinoy; Kumar, Shubham; Joshi, Krati; Govindaraja, Thillai; Krishnamurty, Sailaja; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2020)
Nanoscopic modifications leading to multi-dimensional graphene structures are known to significantly influence their candidature for several applications including catalysis, energy storage, molecular sensing and most significantly adsorption and remediation of harmful materials such as dyes. The present work attempts to identify the key trajectories that connect the structural qualification with a chosen application, viz., the interactive forces in dye remediation. Various physico-chemically Modified Graphene Nanostructures (MGNs) such as 2 dimensional Graphite, Graphene Oxide (GO), reduced GO (rGO), holey rGO, and 3 dimensional GO hydrogel and Holey GO hydrogel are chosen and synthesised herein. These represent varieties of physicochemical features with respect to their dimensionality, surface features such as oxygen functionality, nanoscopic holes etc., that contribute to their characteristic overall surface interactions. Methylene Blue (MB), a popular industrial effluent posing major environmental concern is chosen to be a probe adsorbate in this case study. An exclusive real time in-situ UV visible spectral experiment provides the revealing reasons behind the outstanding performance of 2D GO sheets with an adsorption capacity of greater than 92 % even at high MB concentrations (>2000 ppm). A complex dependency of various factors such as surface oxygen, morphology, nanoporosity etc. on the unique overall interaction with an adsorbent such as MB by all these adsorbates is demonstrated using experimental and DFT based computational studies. Electrostatics and hydrogen bonding are understood to be the two dominant forces driving the MB adsorption on the best performing GO here.
Keywords: Density functional theory; In-situ UV-vis spectroscopy; Interactions; Methylene blue; Modified Graphene Nanostructures

Atom-economical and scalable asymmetric synthesis of daridorexant key starting material (S)-2-methylproline via the memory of chirality - Bhatt, Gaurang J.; Kumar, Shubham; Mhaske, Santosh B. (Organic Process Research & Development, 2025)
alpha-Methylproline is a key starting material (KSM) for important drugs, such as Daridorexant, Veliparib, Trofinetide, Enlicitide chloride, and Usnoflast. A practical and scalable asymmetric synthesis of (S)-2-methylproline and its derivatives has been disclosed here using a diketopiperazine intermediate-based strategy that leverages the memory of chirality. Commencing from an inexpensive starting material, l-proline, it proceeds through dimerization and alkylation, followed by hydrolysis under mild conditions, avoiding column chromatography to furnish enantiomerically pure (S)-2-methylproline.HCl, which was also converted to (S)-Boc-2-methylproline and (S)-2-methylproline methyl ester.HCl. In contrast to prior multistep approaches, which rely on expensive chiral auxiliaries and hazardous reagents, this concise three-step route offers operational simplicity, scalability, and superior stereochemical control, making it an attractive method for the synthesis of proline-derived building blocks for peptidomimetics and pharmaceutical applications.
Keywords: alpha-methylproline; atom economy; memoryof chirality; Stereoselective

Deciphering the comprehensive microbiome of glacier-fed Ganges and functional aspects: implications for one health - Samson, Rachel; Kumar, Shubham; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (Microbiology Spectrum, 2025)
Glacier-fed rivers are significant ecological components of the river catchments, yet their microbial diversity and the associated antimicrobial potential remain underexplored. The Ganges is a glacier-fed river of immense cultural, religious, and ecological significance that supports over 400 million people downstream, providing essential water for agriculture, industry, and daily use. Despite its importance, the microbial community composition and antimicrobial potential, across its relatively pristine origin, remain largely underexplored. One possible explanation for this could be the lower microbial load in the upstream glacier-fed region, which likely results in a reduced DNA yield, insufficient for whole-metagenome sequencing, in contrast to the more biologically diverse and nutrient-rich lower reaches. In this study, we developed an efficient DNA extraction and amplification method using low-input DNA to sequence the microbiome from sediments of the glacier-fed Ganges River in pre-monsoon and post-monsoon over 2 years. Taxonomic and functional diversity of bacterial and viral (phage) communities were analyzed, together with the seasonal variations in their composition. Significant differences in microbial communities were observed in response to seasonal shifts (P < 0.05). During the dry season, Proteobacteria and Actinobacteria were predominant, while Bacteroidetes and Firmicutes were abundant post-monsoon (P < 0.05). The microbiome harbors potential for the biosynthesis of streptomycin, phenylpropanoid, penicillin, and cephalosporins. Bacteriophages from Podoviridae, Myoviridae, and Siphoviridae showed lytic potential against putrefying and pathogenic bacteria. This first comprehensive study on the glacier-fed Ganges River highlights significant seasonal shifts in microbial diversity. The initial insights into the functional profile of the bacterial and phage diversity offer opportunities to explore various natural compounds and enzymes to tackle antimicrobial resistance under the one-health canopy.
Keywords: Bacteriophages; glacier-fed-Ganges; Microbiome; Secondary metabolites; special properties

Long-term genomic surveillance of SARS-CoV-2 in campus wastewater depicts lineage trends and public health implications during and after omicron waves - Pramanik, Rinka; Rajput, Vinay; Malik, Vinita; Nannaware, Kiran; Matra, Sejal; Joshi, Sai; Kumar, Shubham; Samson, Rachel; Yadav, Rakesh Kumar; Shah, Priyanki; Shashidhara, LS; Dastager, Syed; et al. (Environment & Health, 2025)
SARS-CoV-2 transmission and detection on academic campuses in low- to middle-income countries has not been explored. The present study explored wastewater surveillance of SARS-CoV-2 in a campus setting in Pune, Maharashtra, India, offering insights into variant-specific trends and their correlation with clinical cases over a 2.5 year period from November 2021 to April 2024. We collected 242 wastewater samples from the campus sewershed and processed them to extract RNA and perform RT-qPCR and sequencing, followed by lineage assignment using the LCS tool. Early signals of different SARS-CoV-2 variants, such as BA.2.X, JN.1.X, and KP.2.X, were detected in wastewater prior to its first clinical report in Maharashtra, India. Wastewater viral load strongly correlated with clinical cases during the Omicron phase (ρ = 0.73–0.81) compared to the post-Omicron phase (ρ = −0.06 to 0.31). This study also highlights that alerts and warnings issued on the basis of wastewater viral hikes have proven instrumental in preventing outbreaks of SARS-CoV-2 variants on campus. However, downgrading COVID-19 from pandemic status by the WHO resulted in a subsequent decrease in public vigilance, changing the viral dynamic in the last phase of the study. This study showcases the utility of wastewater surveillance in a campus setting as an early warning system and understands the interplay of public health policy effects in viral dynamics within controlled ecosystems, such as campuses or offices.